Factors controlling sedimentation in the Toruń-Eberswalde ice-marginal valley during the Pomeranian phase of the Weichselian glaciation: an overview - Pisarska-Jamroży, Małgorzata (Bogucki Wydawnictwo Naukowe, 2015)
During the Pleistocene the Scandinavian ice sheet drained huge quantities of sediment-laden meltwaters. These meltwaters supplied ice-marginal valleys that formed parallel to the front of the ice sheet. Not without significance was the supply of ice-marginal valleys from extraglacial rivers in the south. Moreover, periglacial conditions during and after sedimentation in ice-marginal valleys, the mor -phology of valley bedrocks, and erosion of older sediments played important roles in the depositional scenarios, and in the mineralog -ical composition of the sediments. The mechanisms that controlled the supply and deposition in ice-marginal valleys were analysed on the basis of a Pleistocene ice-marginal valley that was supplied by northern and southern source areas in the immediate vicinity. Investigations were conducted in one of the largest ice-marginal valleys of the Polish-German lowlands, i.e., the Toruń-Eberswalde ice-marginal valley, in sandurs (Drawa and Gwda) supplied sediments and waters from the north into this valley, and on extraglacial river terraces (pre-Noteć and pre-Warta rivers), formed simultaneously with the sandurs and ice-marginal valley (Pomeranian phase of Weichselian glaciation) supplied sediments and waters from the south into this valley. A much debated question is how similar, or different, depositional processes and sediments were that contributed to the formation of the Toruń-Eberswalde ice-marginal valley, and whether or not it is possible to differentiate mostly rapidly aggraded sandur sediments from ice-marginal valley sediments. Another question addresses the contribution of extraglacial feeding of the Toruń-Eberswalde ice-marginal valley. These matters were addressed by a wide range of analyses: sediment texture and structure, architectural elements of sediments, frequency of sedimentary successions, heavy-mineral analysis (both transparent and opaque heavy minerals), analysis of rounding and frosting of quartz grains, and palaeohydrological calculations. Additionally, a ...